Exploring Pathways to Work through Skills Development in Sport for Youth with Intellectual Disabilities in Metropolitan Zimbabwe - Kasu, Sandra (Division of Disability Studies, 2022)
Background Youth with intellectual disabilities usually experience poorer post-school outcomes than youth with any other disabilities and youth in the general population (McConkey, Dowling, Hassan & Menke, 2013). Youth with intellectual disabilities are often marginalized and discriminated against regarding skills development and work opportunities as society seems to place high value on an individual's intellect (International Labour Organisation, 2015). However, international experience shows that youth with intellectual disabilities can become valuable employees with adequate training (Scheef, 2016). Participation in sports has shown to have a positive correlation with quality of life, satisfaction with life, community reintegration, and mood as well as employment opportunities for persons with disabilities (Diaz, Miller, Krauz & Fredericson, 2019). Hence it became useful to explore skills development and vocational training opportunities in sports that could facilitate youth with intellectual disabilities to access work skills training and work opportunities in urban Zimbabwe. Aim The overall aim of the study was to explore how participation in activities related to sports organisations and events enables youth with intellectual disabilities to access livelihood opportunities to become economically active. Objectives The objectives of the study were: 1. To identify any possible skills development and vocational training opportunities for youth with intellectual disabilities in sports events and organisations in Zimbabwe. 2. To describe the personal factors of youth with intellectual disabilities that enable them to access skills development and vocational training. 3. To identify environmental factors that enable youth with intellectual disabilities to access self-employment, supported employment or formal employment. 4. To determine the role of family, caregivers, and guardians in shaping the livelihood options of youth with intellectual disabilities. 5. To determine the role of skills trainers in developing the pre-vocational skills and vocational training in general for youth with intellectual disabilities. 6. To determine the role of sports coaches and managers in shaping the life skills' development of youth with intellectual disabilities who partake in sports. Methodology The research was a qualitative study in the form of critical ethnography. Critical ethnography speaks on behalf of minority groups such as the point of view of youth with intellectual disabilities' by stating what is and how it can be changed (Duff, Rogers, and Ross, 2016). The design was a collective study as more than one study site was used. The research took place at two adult vocational training centres for youth with intellectual disabilities and at three sports events. Participants were recruited by purposive sampling. Six youths with intellectual disabilities, five parents, caregivers, or guardians of youth with intellectual disabilities, two sports managers or organisers, two sports coaches and two skills trainers of youths with intellectual disabilities participated in the study to make a total sample size of seventeen. Participation observations, semi-structured interviewing and reflective journaling were used as data collection methods. Findings Untapped work opportunities were identified for youth with intellectual disabilities who participated in sports; however, they remained as lost opportunities as they were not being fully utilized. The youths had potential enablers for employability, but they were not being given access to work opportunities. The youths were invisible to potential employers owing to the remote location of their vocational training centres. Female youths were being prejudiced regarding livelihoods' development owing to the remote nature of the training centres, which made it unsafe for them to travel there. There were limited resources for the livelihoods' development of the youth due to economic hardships the country was facing. The government's support for livelihoods' development of the youth was inadequate. Families, peers, and the community were segregating youth with intellectual disabilities, which had the effect of disempowering them and their parents regarding the youths' livelihoods' development. The parents had shared feelings of fear and anxiety over what would become of their youth once they finished school or if their parents died. There was a lack a collective action amongst the parents regarding the youths' livelihoods' development. The parents' support regarding their children's livelihoods' development was inadequate and their knowledge on how to enhance their youths' livelihoods development was insufficient. The parents were also not getting sufficient support from society to empower their youth. The youths with intellectual disabilities were often left out of economic activities at sports events and in the greater community. The sports coaches and skills trainers were not actively planning or advocating for the youths to participate in economic activities at sports events. Conclusion This study explored the livelihoods' developments that were possible for youths with intellectual disabilities through their participation in sports. It was necessary to find effective ways to develop youths with intellectual disabilities' opportunities to become economically active as engagement in work activities is a basic human right. This study established that the parents of the youths needed to take the initiative regarding the livelihoods' development of their children. The youths and their parents needed to take collective action and find their political voice to advocate for skills training and work opportunities to the training centres, the community, and potential employers as well as the government. The parents needed to take their negative perceptions, which were acting as indirect blocks and which were disempowering them, as motivators to enact positive change for their children's livelihoods' development. It was necessary for parents, skills trainers, and sports coaches to market the youths to potential employers. At the training centres, the administration, skills trainers, and sports coaches need to consider a curriculum change to include a work attachment for the youth in inclusive employment. Sports coaches and skills trainers need to teach life skills intentionally that are transferrable in work situations and provide the youth with opportunities to practice the skills learnt in work settings. The sports coaches and skills trainers needed further training on how to use sports participation as a medium to enhance the youths' livelihoods' development. Sports managers needed to incorporate youth with intellectual disabilities and their training schools in economic activities in sports organisations and at sports events. Female youths with intellectual disabilities needed to be encouraged to attend the vocational training centres by providing for their interests and providing them with safe transportation to attend the vocational training centres.